2005
DOI: 10.1073/pnas.0408871102
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of viral infectivity through lethal defection

Abstract: RNA viruses replicate with a very high error rate and give rise to heterogeneous, highly plastic populations able to adapt very rapidly to changing environments. Viral diseases are thus difficult to control because of the appearance of drug-resistant mutants, and it becomes essential to seek mechanisms able to force the extinction of the quasispecies before adaptation emerges. An alternative to the use of conventional drugs consists in increasing the replication error rate through the use of mutagens. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
216
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(231 citation statements)
references
References 25 publications
11
216
3
1
Order By: Relevance
“…Since mutagens are not expected to act as chain terminators, no significant decrease in viral DNA would be expected from compounds acting as lethal mutagens. In fact, previous studies have demonstrated that even when mutagens eliminate infectivity, there are still detectable levels of viral RNA (13). This is likely due to the production of defective viruses that are not infectious and can interfere with the infectivity of viruses that were not lethally mutagenized, a process known as lethal defection (13).…”
Section: Discussionmentioning
confidence: 99%
“…Since mutagens are not expected to act as chain terminators, no significant decrease in viral DNA would be expected from compounds acting as lethal mutagens. In fact, previous studies have demonstrated that even when mutagens eliminate infectivity, there are still detectable levels of viral RNA (13). This is likely due to the production of defective viruses that are not infectious and can interfere with the infectivity of viruses that were not lethally mutagenized, a process known as lethal defection (13).…”
Section: Discussionmentioning
confidence: 99%
“…Extinction through lethal defection was first observed in persistent infections of lymphocytic choriomeningitis virus (LCMV) treated with the mutagen 5-fluorouracil (5-FU). About 90 h post-infection, the ability of the virus to produce infective particles disappeared, though its replicative capacity, understood as the capacity of an RNA virus to produce RNA progeny, was not affected (Grande-Pérez et al 2005). The interpretation of the experiment was as follows.…”
Section: The Role Of Defective Formsmentioning
confidence: 99%
“…The production and maintenance of defectors and the selection of different traits in different environments may offer an alternative pathway to extinction, as has been suggested (Grande-Pérez et al 2005) and theoretically demonstrated (Iranzo & Manrubia 2009). The key for a phenotypic trait to become useless requires (i) an environment where that trait is either neutral or not subject to strong selection and (ii) a finite number of individuals in the quasispecies, since extinction through the action of defectors is a purely stochastic phenomenon.…”
Section: The Critical Mutation Rate: a Relative Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Within-host diversity may be achieved when inoculum comprises a diverse pool of virus genomes (Lord et al 1997;Bonneau et al 2001;Cory et al 2005;Herring et al 2005;Jerzak et al 2005), when genotypically distinct viruses cooperate to achieve infection, such as the facilitation observed in homologous or heterologous 'helper viruses' (Eckner 1973;Stenger 1998), or when viruses are capable of generating de novo diversity during the replication process in the newly infected host (Domingo et al 1998;Chang et al 2002;Ló pez-Bueno et al 2003). Genotypic diversity within infected hosts can have dramatic repercussions for both host and virus, including alterations in virulence (harm suffered by the host) (Sedarati et al 1988;Brown et al 2002;Schjørring & Koella 2002;Alizon 2008), within-host population dynamics (Miralles et al 2001;Rauch et al 2008), virus fitness (Hodgson et al 2004;Arends et al 2005;Č ičin-Š ain et al 2005;Simó n et al 2006), and if frequent, may favour the evolution of cheating genotypes (Turner & Chao 1999;Frank 2000;Grande-Pérez et al 2005).…”
Section: Introductionmentioning
confidence: 99%